O esforço em inovação e sua associação com o ambiente competitivo: um estudo das empresas listadas na B3 - Dall'Agnol, Marlise (Universidade do Vale do Rio dos Sinos, 2020)
Innovation is considered an essential source of growth and productivity gains for companies, in addition to promoting benefits for the entire economy. Companies, to guarantee competitive advantage, must adapt their strategies to their competitive environment, employing efforts in innovation to ensure their market share and long-term sustainability. In this context, this study aims to analyze the association between the innovation effort and the competitive environment, this restricted to competition, of companies in the sectors of publicly traded Brazilian industry. To carry out the research data collection was performed in the Financial Statements and Economática® for a sample of 96 companies, covering the period from 2010 to 2018. The methodology adopted was the regression for panel data with random effects using statistical software Stata®. The result of the research model suggests that companies operating in more competitive markets invest more in innovation, corroborating Schumpeter's (1934) assumptions about the process of creative destruction. For the stock volatility variable, the model suggests more significant investment in innovation by companies that accept the degree of risk concerning fluctuations in their stock market prices. By observing the internal determinants, it is possible to identify that larger companies invest more in innovation, potentially due to the structural and market advantages they have. On the other hand, the results also suggest that companies that present higher profitability and a higher level of indebtedness (short and long term) have fewer efforts in innovation, which may be related to the uncertainties and associated risks, which end up discouraging the use of new resources, either own or from third parties, in such investments. Thus, the present work contributes to the literature by bringing new evidence of the influence of market dynamics and internal determinants on the decision of companies to invest their resources in innovation efforts.
Keywords: Inovação; Ambiente competitivo; Concentração de mercado; Volatilidade das ações; Vantagem competitiva; Innovation; Competitive environment; Market concentration; Stock volatility; Competitive advantage; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis